2014
DOI: 10.2495/wp140231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Moringa-treated wastewater on drip-irrigated sandy loam soil

Abstract: Moringa oleifera seeds possess coagulating and antimicrobial properties for wastewater treatment. This paper reports the chemical and biological analyses of wastewater samples from the university hostel (W 1), the main abattoir (W 2) and the Nigerian Bottling Company, NBC (W 3) in Maiduguri, Nigeria; treated with Moringa seed solution concentration (MOSC) at 0 (Control), 10, 20, 30 and 40% levels. The treated wastewater was used for irrigating Amaranthus hybridus under drip irrigation on sandy loam soil on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Oxisols, contrairly, were located in Brazil and all of them were clayey soils, which is commonly aggregated in a strong grade of fine and very fine granular structure (Eswaran and Reich, 2004), leading to a rapid permeability. Regarding soil texture in the reviewed database, 31.03% of papers did not mention it (Adesemoye et al, 2006;Araujo et al, 2019;Bole and Gould, 1985;Shilpi et al, 2018), 27.59 % studied sandy loam soils (Abegunrin et al, 2016c;Arku and Musa, 2014;Sims, 2003b, 2000;Russell, 1982;Russell et al, 1993;N Wells and Whitton, 1970), 13.79% silt loam Churchman and ate, 1986;Magesan et al, 1999), 10.34 % clay Oliveira et al, 2017a;Oliveira et al, 2017b), 10.34% sand da Silva Neto et al, 2013;Osemwota, 2010b), 3.45% clay loam (A. and 3.45% loamy sand (Russell, 1982).…”
Section: Soil Classification and Soil Quality Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxisols, contrairly, were located in Brazil and all of them were clayey soils, which is commonly aggregated in a strong grade of fine and very fine granular structure (Eswaran and Reich, 2004), leading to a rapid permeability. Regarding soil texture in the reviewed database, 31.03% of papers did not mention it (Adesemoye et al, 2006;Araujo et al, 2019;Bole and Gould, 1985;Shilpi et al, 2018), 27.59 % studied sandy loam soils (Abegunrin et al, 2016c;Arku and Musa, 2014;Sims, 2003b, 2000;Russell, 1982;Russell et al, 1993;N Wells and Whitton, 1970), 13.79% silt loam Churchman and ate, 1986;Magesan et al, 1999), 10.34 % clay Oliveira et al, 2017a;Oliveira et al, 2017b), 10.34% sand da Silva Neto et al, 2013;Osemwota, 2010b), 3.45% clay loam (A. and 3.45% loamy sand (Russell, 1982).…”
Section: Soil Classification and Soil Quality Indicatorsmentioning
confidence: 99%
“…In relation to soil pH, nine works reported a decrease of soil pH when the slaughterhouse effluent was applied Da Silva Neto et al, 2013;Sims, 2003, 2000;Balaji Seshadri et al, 2014) while three others reported an increase in soil pH (Oliveira et al, 2017b;Arku et al, 2014;Osemwota, 2010). Most works relate such decrease in soil pH with oxidation of organic compounds and with the lower pH of the applied effluent (Guo and Sims, 2000;, as well as the process of nitrification, which releases ions of H + (Da Silva Neto, 2013;.…”
Section: Impact Of Irrigation With Slaughterhouse Effluent On Soil Qu...mentioning
confidence: 99%